D.light Design : marketing channel strategies in India - Coughlan, Anne T., (SAGE knowledge. Cases., 2016)
This case looks at a new start-up company, d.light Design, as it was seeking to go to market in India with its solar-powered LED lamps in 2009. Sam Goldman, founder and chief customer officer of d.light, was in New Delhi, India; his business-school friend and co-founder Ned Tozun was in China, the site of the company's manufacturing plant.